Economic potential of vertical farms in Slovakia - Mičieta, Jakub (2025)
The diploma thesis explores the economic potential of vertical farms in Slovakia. Vertical farming is experiencing growth, as it proposes an innovative agriculture method with the use of new technologies and techniques. These allow year-round farming that has higher yield, improved space efficiency, water preservation, shorter supply chain and other advantages. Nevertheless, the use of numerous technologies drives up the electricity consumption and initial investment, resulting in the majority of farms being unprofitable. Apart from this, the intensive labor requirements and limited selection of economically viable crops remain an issue. In the context of Slovakia, vertical farms have the ability to solve local problems, such as the low fertility of land in certain regions or shorten the supply chain. However, the high operating expenses and the inability to receive subsidies undermine their competitiveness in the Slovak market, where the price remains the main selling factor for consumers. The model of profitability conducted for a vertical farming container supports these findings.